2020
DOI: 10.1002/jsfa.10465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of a previous 150‐MPa treatment on the quality loss of frozen hake stored at different temperatures

Abstract: BACKGROUND:This study was addressed to the quality loss of European hake (Merluccius merluccius) during frozen storage. Its objective was to comparatively analyse the effect of a previous high-pressure processing (HPP) (150 MPa for 2 min) when different storage temperatures (-10, -18 and -30 ºC) were employed. RESULTS:Most chemical quality indices (trimethylamine, TMA; dimethylamine, DMA, formaldehyde, FA; free fatty acids, FFA) provided a marked content increase with freezing and frozen storage time, values b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The content of TBARS and FFA were negatively correlated with SSP, Ca 2+ -ATPase, and SH. As stated above, the content of TBARS and FFA both significantly increased with frozen storage time, indicating that the hydrolysis and oxidation of lipids may mutually promote the values as reported in other studies [8,47]. Differently, the content of SSP, Ca 2+ -ATPase, and SH were all significantly decreased under frozen storage as shown above.…”
Section: Total Sulfhydryl (Sh) Contentsupporting
confidence: 76%
See 2 more Smart Citations
“…The content of TBARS and FFA were negatively correlated with SSP, Ca 2+ -ATPase, and SH. As stated above, the content of TBARS and FFA both significantly increased with frozen storage time, indicating that the hydrolysis and oxidation of lipids may mutually promote the values as reported in other studies [8,47]. Differently, the content of SSP, Ca 2+ -ATPase, and SH were all significantly decreased under frozen storage as shown above.…”
Section: Total Sulfhydryl (Sh) Contentsupporting
confidence: 76%
“…In addition to species, preservation methods such as brine showed a lower response of FFA content during frozen storage according to what was reported previously [34]. In the end, the content of FFA at 261 K was elevated to 39.46 ± 9.89 g/100 g, which was 2.35 and 4.42 times as high as the concentration at 253 K and 245 K. Also, FFA concentration at 261 K was consistently more than that at 253 K and 245 K. These results indicated that FFA still formed during freezing, but the hydrolysis of lipids was significantly suppressed at lower temperatures [8].…”
Section: Free Fatty Acids (Ffa)mentioning
confidence: 82%
See 1 more Smart Citation
“…Consequently, chemical changes that are normally expected to happen in foods during processing such as lipid oxidation not related to contaminants (e.g. in Wiggers et al., 2004; Gou et al., 2010; Escobedo‐Avellaneda et al., 2011; Borda et al., 2013; Medina‐Meza et al., 2014; Yi et al., 2017; Carrera et al., 2020) are not considered.…”
Section: Assessmentmentioning
confidence: 99%